Air Pollution and Economic Development in KSA: Environmental Kuznets Curve and Implications for Sustainable Development - Abid, Mehdi; Gheraia, Zouheyr; Sekrafi, Habib; Abdelli, Hanane (International Journal of Energy Economics and Policy, 2024)
In a global context increasingly concerned about climate hazards, understanding the impact of economic growth on the environment is becoming crucial, especially for developing countries. This paper addresses this issue through the lens of carbon dioxide (CO2) emissions and examines how economic growth affects the environment in the case of KSA. The objective of this study is to test the validity of the environmental Kuznets curve over the period 1990-2020 using the Granger causality test. The results of the test indicate a long-term relationship between the variables, and the results of the long-term model confirm the environmental Kuznets curve hypothesis for the Saudi economy with a GDP per capita turning point of US$ 19977,794. The results suggest that there is a bi-directional, short-term causal relationship. The long-term causality is unidirectional from income to CO2 emissions. Our results suggest that the KSA should distinguish between economic policy and environmental policy to improve its environmental quality. Economic expansion leads to an increase in the level of pollution and the concentration of GHGs in the atmosphere if the government does not take the necessary precautions.